Humor v antologijah Enci benci na kamenci - Fink, Katarina (Revija za elementarno izobraževanje, 2012)
Humour in the Anthologies Encibenci na kamenci. The humour which appears in Slovenian children’s folk tradition is supported by various theories. Attardo claims that Plato and Aristotle are two main representatives of the theory of superiority, according to which laughing is a result of the realisation that the one who laughs is better than the one who does not. Immanuel Kant and Artur Schopenhauer, on the other hand, are representatives of the mismatch theory based on the (reality of) conflict between the concept and the object. In his work Esej o smehu, Bergson proves that any mistake can become humorous, yet we also tend to like the funny character from the very beginning. In Mala literarna teorija (1995), Slovenian theorist Matjaž Kmecl states that humour is an ethological form characterised by cheerful carefree mood/behaviour, smiling as a means to distance oneself from unease, mental balance of the personas, and mental attitude towards the world. As regards children’s literature, we have to consider the reader’s/listener’s age which is a key factor in what children perceive as funny as well as the circumstances such as real time, general cultural level, and social status of the child. Humour plays different roles in children’s folk tradition. Nonsense humour combines the indirect cognitive aspect with the apparently entertaining aspect. As the word itself suggests, the aim of educational humour based on a comic child character who is far from being a role model is to educate and to entertain. Last but not least, there is the humour of contradiction, which is expressed in taboos. All the poems discussed herein are taken from children’s folk tradition and are demonstrations of concrete examples and characteristics, which classify them as literary works with humorous elements.